Odpowiedzi

Najlepsza Odpowiedź!
2010-02-05T14:15:15+01:00
5NO₂⁻ + 2MnO₄⁻ + 6H+ --> 5NO₃⁻ + 2Mn²+ + 3 H₂O
N³ ---> N⁵ + 2elektrony |×5
Mn⁷ + 5 elektronów --> Mn² |×2

3 As2S3 + 28 HNO3 + 4 H2O = 6 H3AsO4 + 9 H2SO4 + 28 NO
2 As3+ --> 2 As5+ + 4elektrony |× 3
N5+ + 3 elektrony ---> N2+ | × 4

2NaNO3 + 2FeSO4 + 2H2SO4 = Na2SO4 + Fe2(SO4)3 + 2NO + 2H2O
Fe2+ --> Fe3+ + 1 elektron
N3+ + 1 elektron --> N2+

5H2O2 + 2MnO4- + 6H+ = 5O2 + 2Mn 2+ + 8H2O
2O-1 --> O2 + 2 e |× 5
Mn7+ + 5 e ---> Mn2+ | ×2

Bi2S3 + 2NO3- + 8H+ = 2Bi3+ + 3S + 2NO + 4H2O
3S2- ---> 3S + 6e |× 1
N5+ + 3e ---> N2+ |× 2

MnO4- + 5Fe2+ + 8H+ = Mn2+ + 5Fe3+ + 4H2O
Mn7+ + 5e --> Mn2+ |× 1
Fe2+ --> Fe3+ + 1e |× 5

Cr2O72- + 6I- + 14H+ = 2C33+ + 3I2 + 7 H2O
2Cr6+ + 6e --> 2Cr3+
2I- --> I2 + 2e |× 3

BrO3- + 6I- + 6H+ = 3I2 + Br- + 3H2O
br5+ + 6e ---> Br-
2I- ---> I2 + 2e |× 3

3PbS + 8HNO3 = 3S + 3Pb(NO3)2 + NO = 4H2O
S-2 ---> S + 2e | ×3
N5+ + 3e ---> N2+ |× 2

HClO4 + 4H2SO3 = HCl + 4H2SO4
Cl7+ + 8e ---> Cl-
S4+ ---> S6+ + 2e |× 4